Targeted modulation of cell differentiation in distinct regions of the gastrointestinal tract via oral administration of differently PEG-PEI functionalized mesoporous silica nanoparticles - Desai D (Dove Medical Press, 2016)
Diti Desai,1–4 Neeraj Prabhakar,2 Veronika Mamaeva,3,5 Didem Şen Karaman,2,4 Iris AK Lähdeniemi,1,6 Cecilia Sahlgren,3,7,* Jessica M Rosenholm,2,4,* Diana M Toivola1,6,* 1Cell Biology, Faculty of Science and Engineering, Åbo Akademi University, Turku, Finland; 2Pharmaceutical Sciences Laboratory, Faculty of Science and Engineering, Åbo Akademi University, Turku, Finland; 3Turku Centre for Biotechnology, University of Turku and Åbo Akademi University, Turku, Finland; 4Laboratory of Physical Chemistry, Faculty of Science and Engineering, Åbo Akademi University, Turku, Finland; 5Department of Clinical Science, University of Bergen, Bergen, Norway; 6Turku Center for Disease Modeling, Institute of Biomedicine, University of Turku, Turku, Finland; 7Department of Biomedical Engineering, Technical University of Eindhoven, Eindhoven, the Netherlands *These authors contributed equally to this work Abstract: Targeted delivery of drugs is required to efficiently treat intestinal diseases such as colon cancer and inflammation. Nanoparticles could overcome challenges in oral administration caused by drug degradation at low pH and poor permeability through mucus layers, and offer targeted delivery to diseased cells in order to avoid adverse effects. Here, we demonstrate that functionalization of mesoporous silica nanoparticles (MSNs) by polymeric surface grafts facilitates transport through the mucosal barrier and enhances cellular internalization. MSNs functionalized with poly(ethylene glycol) (PEG), poly(ethylene imine) (PEI), and the targeting ligand folic acid in different combinations are internalized by epithelial cells in vitro and in vivo after oral gavage. Functionalized MSNs loaded with γ-secretase inhibitors of the Notch pathway, a key regulator of intestinal progenitor cells, colon cancer, and inflammation, demonstrated enhanced intestinal goblet cell differentiation as compared to free drug. Drug-loaded MSNs thus remained intact in vivo, further confirmed by exposure to simulated gastric and intestinal fluids in vitro. Drug targeting and efficacy in different parts of the intestine could be tuned by MSN surface modifications, with PEI coating exhibiting higher affinity for the small intestine and PEI–PEG coating for the colon. The data highlight the potential of nanomedicines for targeted delivery to distinct regions of the tissue for strict therapeutic control. Keywords: intestinal targeting, PEG-PEI copolymer, Notch inhibition